1996
DOI: 10.1017/cbo9780511624919
|View full text |Cite
|
Sign up to set email alerts
|

The Principles of Mathematics Revisited

Abstract: This book, written by one of philosophy's pre-eminent logicians, argues that many of the basic assumptions common to logic, philosophy of mathematics and metaphysics are in need of change. It is therefore a book of critical importance to logical theory. Jaakko Hintikka proposes a new basic first-order logic and uses it to explore the foundations of mathematics. This new logic enables logicians to express on the first-order level such concepts as equicardinality, infinity, and truth in the same language. The fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
156
0
10

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 296 publications
(168 citation statements)
references
References 0 publications
2
156
0
10
Order By: Relevance
“…[13] or [15]). In this extension of predicate logic it can be indicated that a quantifier is independent of some of the quantifiers with larger scope.…”
Section: The Representations Of the De Dicto -De Re Readingsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] or [15]). In this extension of predicate logic it can be indicated that a quantifier is independent of some of the quantifiers with larger scope.…”
Section: The Representations Of the De Dicto -De Re Readingsmentioning
confidence: 99%
“…The first example (in 1974) concerned natural language semantics: the branching quantifier sentences [12]. Later the de dicto -de re ambiguity and other scope ambiguities were mentioned, and as examples in mathematics the definitions of continuity and uniform continuity [13]. Many more examples of applications are given in [13].…”
Section: The Representations Of the De Dicto -De Re Readingsmentioning
confidence: 99%
“…Independence Friendly logic [4] (IF, for short) is an extension of first-order logic (FO) where each disjunction and each existential quantifier may be decorated with denotations of universally-quantified variables, as in:…”
Section: Introductionmentioning
confidence: 99%
“…Since the expressive power of IF corresponds to that of existential secondorder logic (Σ 1 1 ) [4,5] and Σ 1 1 is not closed by (classical) negation, it is clear that classical negation cannot be defined in IF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation